KEBUDAYAAN MASYARAKAT TORAJA DALAM NOVEL PUYA KE PUYA KARYA FAISAL ODDANG (INTERPRETASI SIMBOLIK CLIFFORD GEERTZ) - Priyandini, Ema; Al-Ma’ruf, Ali Imron; Hasyim, Nafron (Fon : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research is based on the culture in Indonesia, one of which is the culture of the Toraja people. The purpose of this research is to describe the symbolic interpretation in the novel Puya ke Puya by Faisal Oddang. This research uses descriptive qualitative research with literary anthropology approach. The data of this research are words, phrases, statements, expressions, and discourses related to Clifford Geertz's symbolic interpretation in the novel Puya ke Puya by Faisal Oddang. Secondary data sources include books on the subject. Data collection techniques use reading and note-taking techniques. hermeneutic techniques are data analysis techniques used in this research. The result of this research is data in the form of Clifford Geertz's symbolic interpretation which includes: (1) Represented plans include traditional songs and traditional clothing. (2) The Toraja people's recipe that is represented is tanu kerbau. (3) Represented Torajan rules are the noble strata and the ma’tinggoro tedong. (4) Represented Torajan instructions are aluk todolo belief and Rambu Solo ritual.